Oxidative stress biomarkers and asthma characteristics in adults of the EGEA study - Andrianjafimasy, Miora; Zerimech, Farid; Akiki, Zeina; Huyvaert, Helene; Le Moual, Nicole; Siroux, Valérie; Matran, Régis; Dumas, Orianne; Nadif, Rachel (The European respiratory journal, 2017)
Asthma is an oxidative stress related disease, but associations with asthma outcomes are poorly studied in adults. We aimed to study the associations between several biomarkers related to oxidative stress and various asthma outcomes.Cross-sectional analyses were conducted in 1388 adults (mean age 43 years, 44% with asthma) from the Epidemiological Study of the Genetics and Environment of Asthma (EGEA2). Three blood antioxidant enzyme activities (biomarkers of response to oxidative stress) and exhaled breath condensate 8-isoprostanes and plasma fluorescent oxidation products (FlOPs) levels (two biomarkers of damage) were measured. Associations between biomarkers and 1) ever asthma and 2) asthma attacks, asthma control and lung function in participants with asthma were evaluated using regression models adjusted for age, sex and smoking.Biomarkers of response were unrelated to asthma outcomes. Higher 8-isoprostane levels were significantly associated with ever asthma (odds ratio for one interquartile range increase 1.28 (95% CI 1.06-1.67). Among participants with asthma, 8-isoprostane levels were negatively associated with adult-onset asthma (0.63, 0.41-0.97) and FlOPs levels were positively associated with asthma attacks (1.33, 1.07-1.65), poor asthma control (1.30, 1.02-1.66) and poor lung function (1.34, 1.04-1.74).Our results suggest that 8-isoprostanes are involved in childhood-onset asthma and FlOPs are linked to asthma expression.